THE INFLUENCE OF BRAND AWARENESS AND BRAND AMBASSADORS ON BUYING INTEREST WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Nabila Nurhuwaida; Muhammad Sholahuddin (Jurnal Ilmu Manajemen (JIMMU), 2024)
The purpose of this study was to analyze the effect of brand awareness and brand ambassadors on buying interest with brand image as an intervening variable. This research method is quantitative. The data source in this study uses primary data. This study uses a questionnaire data collection method. The population in this study were all Skintific Skincare users in Surakarta city. The sampling technique used was Nonprobability sample with purposive sampling method. The number of samples in this study were 150 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS software. The results of this study are that Brand Awareness has a positive and significant effect on Brand Image. Brand Ambassador has a positive and significant effect on Brand Image. Brand Awareness has a positive and significant effect on buying interest. Brand Ambassador has a positive and significant effect on buying interest. Brand Image variable has a positive and significant effect on buying interest.